Engineering synaptic characteristics of TaOx/HfO2 bi-layered resistive switching device. (9th August 2018) - Kim, Sohyeon; Abbas, Yawar; Jeon, Yu-Rim; Sokolov, Andrey Sergeevich; Ku, Boncheol; Choi, Changhwan
Abstract: We performed various pulse measurements on an atomic layer deposited (ALD) HfO2 -based resistive switching random access memory (RRAM) device and investigated its electronic synaptic characteristics. Unlike requirements for RRAM device application, to achieve the multi-state conductance changes required for the synaptic device, we employed additional sputtered TaOx thin film formation on the ALD HfO2 switching medium, which leads to engineering the concentration of oxygen vacancies and modulating the conductive filaments. With this TaOx /HfO2 bi-layered device, we attained gradual resistive switching, linear and symmetric conductance change, improved endurance and reproducibility characteristics compared to a single HfO2 device. Finally, we emulated spike-timing-dependent plasticity based learning rule with pulses inspired by neural action potential, indicating its potential as an electronic synaptic device in a hardware neuromorphic system.